The Enron-Andersen regulatory review to strengthen auditor independence - Abdullah @ Earnest, Dewi Fariha (Faculty of Management and Human Resource Development, 2004)

(untitled)
The crash of Enron in the US, followed by the worldwide collapse of its auditor, Arthur Andersen (Andersen), has shaken the business world. It was the biggest corporate collapse uncovered in business history. Since then, the investor and public's perception towards the accounting and auditing profession has been badly tarred. Following Enron -Andersen scandal, giant companies like WorldCom, Xerox and WasteManagement faced similar fate. Worst still, the auditors of all these companies are among the Big Fives (now Big Fours). Nevertheless, the reputation of most certified public accountant (CPA) firms are seriously confronting the problems of regaining public's confidence at post-Enron era. Among the major issues elevated was 'auditor independence' of the CPA firms. Arguments rest on the issue of auditor independence and factors like regulatory framework, and business pressures (also corporate governance) that are found to be major contributor to crashes of Enron like. In response to the scandal, the standard-setters, regulators, professions and other related bodies (in the UK and the US) emerged with constructive proposals, which aim to strengthen auditor independence (and corporate accountability). Though, new regulatory have been laid out, the success rate is yet proven. This paper review holds the regulatory scenario depicted in the UK and the US. This is after considering that most of the recent bankrupt cases and regulatory reviews are actively performed in both countries